Dealing with resource curse syndrome in the Ghanaian oil sector through reforms of appropriate laws and policies - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2018)
Mini Dissertation (LLM)--University of Pretoria, 2017.